On g (1,2)^-closed Sets - O. Ravi; R. Bhavani; S. Murugesan; I. Rajasekaran (International Journal of Mathematics And its Applications, 2015)
In this present paper, we introduce a new class of sets namely g (1,2)^-closed sets in bitopological spaces. The notion of g (1,2)^-interior is defined and some of its basic properties are studied. Also we introduce the concept of g (1,2)^-closure in bitopological spaces using the notion of g (1,2)^-closed sets.